The Effect of Employer Branding, Organizational Culture, and Transformational Leadership on the Retention of Millennial Employees at Suzuki Indosarana Cirebon - Nur Afiyah, Nada; Sugiarti, Ade Rizki; Nur Azhaar, Viny Juniarty; Siddiq, Dedi Muhammad (Cirebon Annual Multidiciplinary International Conference (CAMIC), 2026)
Employee retention remains a critical challenge in contemporary human resource management, particularly in managing millennial employees who are characterized by higher job mobility, strong career expectations, and a preference for meaningful work environments. Although prior studies have examined various determinants of employee retention, limited research has simultaneously investigated the roles of employer branding, organizational culture, and transformational leadership within an integrated model, especially in the automotive industry context. Addressing this gap, the present study examines the effects of employer branding, organizational culture, and transformational leadership on millennial employee retention at Suzuki Indosarana Cirebon. This study adopts a quantitative approach using structured questionnaires administered to 60 millennial employees. The data were analyzed using multiple linear regression to evaluate both individual and simultaneous effects of the independent variables on employee retention. The findings reveal that employer branding and transformational leadership exert positive and statistically significant effects on employee retention. Conversely, organizational culture does not demonstrate a significant individual effect. This result may indicate that millennial employees prioritize leadership quality, career development opportunities, and organizational reputation over shared organizational values when making decisions about staying in an organization. Furthermore, the simultaneous test indicates that employer branding, organizational culture, and transformational leadership collectively have a significant effect on employee retention (F = 37.608; p < 0.001), with the model explaining a substantial proportion of variance (Adjusted R² = 0.651). These findings underscore the strategic importance of strengthening employer branding and transformational leadership practices to enhance millennial employee retention, particularly in the automotive industry. The study contributes to the employee retention literature by providing an integrated framework that highlights the relative importance of reputational and leadership-related factors in retaining millennial employees.